1999
DOI: 10.1111/j.1759-5436.1999.mp30002010.x
|View full text |Cite
|
Sign up to set email alerts
|

Elite Perceptions of Poverty: Bangladesh

Abstract: Summaries The Bangladeshi national elite are distanced from and unthreatened by poverty and the poor. Medium‐term solutions to poverty, resting on a belief in the importance of ‘increasing awareness’ through education, rather than in direct public action, are favoured. The poor are viewed as homogeneous, and generally deserving. These benign perceptions may not accord direct anti‐poverty action a high priority on the national agenda, but they also suggest little of the fear which can lead to repressive measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…Changes in teaching processes have thus opened up a larger change agenda that includes addressing the way elites perceive poverty and the poor in Bangladesh (see Hossain and Moore 1999). Through developing their reflexive understanding of one audience-the students-the teachers have come to realize there are other audiences they might serve-in this case, the poor and others who work in fisheries.…”
Section: Reforming Fisheries Education 257mentioning
confidence: 98%
“…Changes in teaching processes have thus opened up a larger change agenda that includes addressing the way elites perceive poverty and the poor in Bangladesh (see Hossain and Moore 1999). Through developing their reflexive understanding of one audience-the students-the teachers have come to realize there are other audiences they might serve-in this case, the poor and others who work in fisheries.…”
Section: Reforming Fisheries Education 257mentioning
confidence: 98%
“…Finally, it has also become clearer that the state also closely shapes the possibilities for political inclusion and empowerment amongst citizens (Houtzager and Moore 2003;IDS 2010). Given that states can be highly capable without necessarily being committed to development, the commitment of political elites to delivering development has also been identified as a critical element of the politics of what works (Booth 2011d;Hossain 2005;Leftwich 1994; Vu 2007). 4 Our findings largely concur with these conclusions, and, in linking this to the underlying role of politics and power relations through the political-settlements perspective, starts to suggest how the conditions within which developmental forms of state capacity and commitment 4 For example, Vu's seminal (2007) comparative study of developmental states in Asia distinguishes between the 'structure' of the state and state-society relations that is required to generate the capacity to deliver development and the 'role' that elites chose to play in committing to this.…”
Section: Which Forms Of State Capacity Matter Most?mentioning
confidence: 99%
“…43 See also the article on middle classes in the edited volume that describes declining inequality in parts of Latin America (López-Calva and Lustig 2010). how structural adjustment led to reduced incomes of public services workers, and how aid money was used in privatization that benefited elites, 44 but this remains rather superficial and pays little attention to the different positions taken by different donors, and contradictions that presumably existed within donors' prescriptions. 45 Naomi Hossain's (2005) work on elite perceptions of poverty in Bangladesh has been one of the few that directly touches on the question posed here, but this too was generally not linked to aid. She concluded that poverty was not a high priority for the Bangladeshi elite, not because they were ignorant or callous about poverty, nor because they failed to see a self-interest in tackling poverty, but simply because it did not have priority: poverty is not perceived as a threat, the elite thought much action was already undertaken, and their distrust of the state reduced appetite for further state-led action.…”
mentioning
confidence: 99%
“…26 Given the sustained public critique of NGOs, both from the political left (seeking a more radical strategy; see Hashemi and Hassan 1999) and the religious-political right (who clashed with NGOs over their adherence to Western cultural values in the early 1990s) it may be remarkable that NGO services have been able to expand as they have in Bangladesh. Certainly, national elite involvement and support in a context of abundant aid have helped to maintain a significant space open for NGOs (Hossain 2005). This space has included a role in the provision of services for which there are strong arguments that the state should supply.…”
Section: Political Spacementioning
confidence: 99%